2016
DOI: 10.1002/pri.1666
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based Practice Intentions and Long-term Behaviours of Physiotherapy Graduates Following an Intensive Education Programme

Abstract: Graduates of an intensive EBP training programme embedded within an existing post-graduate physiotherapy programme regularly implemented EBP in clinical practice. Barriers to evidence implementation were time, access to research and perceived lack of generalizability of research findings. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“…Hunt [43] argues that EBP is also important when professionals work as a team because it helps advance research to establish better methods of patient care. Overall, Perraton et al [44] note that assisting with the PTs' application of research-based knowledge in clinical practice can help enhance the quality of clinical practice and encourage lifelong learning and professional progress.…”
Section: Discussionmentioning
confidence: 99%
“…Hunt [43] argues that EBP is also important when professionals work as a team because it helps advance research to establish better methods of patient care. Overall, Perraton et al [44] note that assisting with the PTs' application of research-based knowledge in clinical practice can help enhance the quality of clinical practice and encourage lifelong learning and professional progress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, health care professionals need to understand the principles of EBP, recognize EBP in action, implement evidence‐based policies, and have a critical attitude to their own practice and to evidence to be able to provide “best practice.” Previous studies demonstrate that most physiotherapists have a positive attitude towards EBP and are interested in learning how to improve their skills in EBP, but its implementation is still deficient . There are some barriers that will impact the physiotherapists ability to implement EBP in the workplace as, eg, lack of time, lack of expertise, difficulty obtaining full‐text articles, inability to understand statistics, lack of support from employers, a limited understanding of scientific research, and misconceptions of the EBP concept …”
Section: Introductionmentioning
confidence: 99%
“…1(p.95) As health care providers, physiotherapists are expected to provide evidence-informed care, 2 and they embrace this responsibility. 3 Yet physiotherapists have identified several barriers to providing evidence-informed care; these barriers primarily relate to awareness of, and access to, relevant research findings as well as lack of time. [3][4][5][6] The medical literature has noted that it takes approximately 17 years for 14% of research findings to be adopted into clinical practice.…”
mentioning
confidence: 99%
“…3 Yet physiotherapists have identified several barriers to providing evidence-informed care; these barriers primarily relate to awareness of, and access to, relevant research findings as well as lack of time. [3][4][5][6] The medical literature has noted that it takes approximately 17 years for 14% of research findings to be adopted into clinical practice. 7 Bridges and colleagues 8 identified that the practicality of gathering evidence, including ease of access, efficiency, and relevance to practice, was associated with greater adoption.…”
mentioning
confidence: 99%